KETERSERAPAN ALUMNI PRODI SEJARAH PERADABAN ISLAM DI DUNIA KERJA LEWAT TRACER STUDY - Asril, Asril; Syauqi, Khilal; Pratama, Fikri Surya (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
One of the challenges facing universities is how to produce graduates who are not only capable of developing knowledge, but who are also able to absorb it quickly and participate in the world of work. The employability of graduates can be demonstrated by the profile of the work they do. Public perception can be measured through a tracer study, which is a study of the track record of graduates. This research is a quantitative study that focuses on tracing the graduates of the History of Islamic Civilisation programme, UIN Imam Bonjol Padang. The results of the tracer study data processing are intended to see the absorption of graduates in the world of work based on suitability with the profile of graduates of the study programme, as well as their absorption in their field of work. The results showed that the percentage of graduates working in relevant fields reached 54%. Another 31% of the graduates decided to become entrepreneurs. The percentage of graduates who were not working was 15%. This remains to be seen, as it comes from the 2022-2023 graduates. Therefore, the socialisation of the profile of graduates to the community and graduate users needs to be improved.